Pemberdayaan Serta Pengembangan Bidang Agama Islam Masyarakat Petemon Surabaya - Sujono, Imam; Nasiri, Nasiri; Isa, Abdullah; Nasiruddin, Atsir Faris; Prastiyo, Rian; Prabowo, Arif Agung; Rohma, Adelia Nur; Fadhilah, Putry; Wijaya, Rahman Benta; Said, Moch Imron; Shodiq, Achmad; Mulyadi, Mulyadi; Ansori, Mukhamad Yusuf; Nuriman, Agus; Arviyah, Vira; Khusniyah, Siti Alfitrotul; Maftuh, Abdullah; Sari, Rosyidah Hikmah; Mustofa, Mustofa; Hadi, Aminulloh; Aufa, Mohammad Zidan (PT. Riset Press International, 2025)
This community service activity through KKN aims to develop a strong religious culture in society, such as increasing worship practices, religion-based social activities, and other religious cultural activities that strengthen the community's Islamic identity. The devotional method is carried out by encouraging cooperation between families in the community in practicing religious values, such as through family study, development of religious human resources, and support between households, as well as developing a strong religious culture in the community, such as increasing the practice of worship, religion-based social activities, and other religious-cultural activities that strengthen the community's Islamic identity. The results of this activity show an increase in the understanding and practice of Islamic teachings in society.